Quality Attributes of Yam (Dioscorea rotundata) Flour as Affected by Some Processing Parameters - B. A, Orhevba; M. O, Ajiboye (Journal of Food Technology Research, 2020)
The effect of slice thickness and blanching time on some properties of yam (Dioscorea rotundata) flour was investigated. The properties determined include moisture content, crude protein, ash content, crude fibre and carbohydrate; bulk density, water and Oil absorption capacity; taste, texture, appearance and aroma respectively. The yam tubers were sliced at 6, 12, 18mm, labeled samples A, B, C and D (control sample) and blanched at 650C for 5, 7 and 9 mins. They were dried at 600C and milled into flour. The results obtained were subjected to statistical analysis using the design expert software 7.0. The results show that slice thickness and blanching time have significant effect (p<0.05) on the fat and ash content which ranged from 3.55 to 9.40% and 1.63 to 2.51% respectively. The slice thickness and blanching time did not have significant effect on moisture content, crude fibre, protein, carbohydrate, bulk density, water absorption capacity and oil absorption capacity of the flour; they ranged from 3.88 to 13.15%, 0.37 to 1.34%, 0.19 to 2.04%, 74.86 to 87.94%, 0.73 to 0.79g/ml, 2.00 to 6.67g/ml, 0.5 to 7.5g/ml respectively. Organoleptic assessment shows that yam flour with slice thickness 18mm and blanched for 5min, 7min and 9 minutes were preferred by panelists in terms of appearance, aroma, texture and taste with mean of 4.6, 4.4, 3.7 and 4.3 respectively. The statistical analysis based on desirability function shows that yam flour sliced at 6mm and 12mm, blanched for 7 minutes respectively yielded yam flour with better nutritional and functional properties.